New massive members of Cygnus OB2 - Berlanas, Sara Rodríguez; Pasquali, Anna; Bertelli Motta, Clio (Astronomy and astrophysics, 2018)
Context. The Cygnus complex is one of the most powerful star forming regions at a close distance from the Sun (~1.4 kpc). Its richest OB association Cygnus OB2 is known to harbor many tens of O-type stars and hundreds of B-type stars, providing a large homogeneous population of OB stars that can be analyzed. Many studies of its massive population have been developed in the last decades, although the total number of OB stars is still incomplete.Aim. Our aim is to increase the sample of O and B members of Cygnus OB2 and its surroundings by spectroscopically classifying 61 candidates as possible OB-type members of Cygnus OB2, using new intermediate resolution spectroscopy.Methods. We have obtained intermediate resolution (R ~ 5000) spectra for all of the OB-type candidates between 2013 and 2017. We thus performed a spectral classification of the sample using HeI-II and metal lines rates, as well as the Marxist Ghost Buster (MGB) software for O-type stars and the IACOB standards catalog for B-type stars.Results. From the whole sample of 61 candidates, we have classified 42 stars as new massive OB-type stars, earlier than B3, in Cygnus OB2 and surroundings, including 11 O-type stars. The other candidates are discarded as they display later spectral types inconsistent with membership in the association. We have also obtained visual extinctions for all the new confirmed massive OB members, placing them in a Hertzsprung-Russell Diagram using calibrations for Teff and luminosity. Finally, we have studied the age and extinction distribution of our sample within the region.Conclusions. We have obtained new blue intermediate-resolution spectra suitable for spectral classification of 61 OB candidates in Cygnus OB2 and surroundings. The confirmation of 42 new OB massive stars (earlier than B3) in the region allows us to increase the young massive population known in the field. We have also confirmed the correlation between age and Galactic longitude previously found in the region. We conclude that many O and early B stars at B > 16 mag are still undiscovered in Cygnus.